Final Validation of the Quality of Life after Brain Injury for Children and Adolescents (QOLIBRI-KID/ADO) Questionnaire - Nicole von Steinbuechel; Marina Zeldovich; Dagmar Timmermann; Ugne Krenz; Inga K. Koerte; Michaela V. Bonfert; Steffen Berweck; Matthias Kieslich; Marlene Henrich; Knut Brockmann; Anna Buchheim; Maike Roediger; et al. (MDPI AG, 2024)
Until recently, no disease-specific health-related quality of life (HRQoL) questionnaire existed for pediatric traumatic brain injuries (TBIs). In this revalidation study, the psychometric properties and the validity of the 35-item QOLIBRI-KID/ADO questionnaire in its final German version were examined in 300 children and adolescents. It is the first self-reported TBI-specific tool for measuring pediatric HRQoL in individuals aged between 8 and 17 years. The six-factor model fits the data adequately. The questionnaire's internal consistency was excellent for the total score and satisfactory to excellent for the scale scores. Intraclass correlations indicated good test-retest reliability, and the measure's construct validity was supported by the overlap between the QOLBRI-KID/ADO and the PedsQL, which measures generic HRQoL. The discriminant validity tests showed that older children and girls reported a significantly lower HRQoL than comparison groups, and this was also true of children who were anxious or depressed, or who suffered from post-concussion symptoms, replicating the results of the questionnaire's first developmental study. Our results suggest that the QOLIBRI-KID/ADO is a reliable and valid multidimensional tool that can be used together with the adult version in clinical contexts and research to measure disease-specific HRQoL after pediatric TBI throughout a person's life. This may help improve care, treatment, daily functioning, and HRQoL after TBI.